A Robust DNA Isolation Protocol from Filtered Commercial Olive Oil for PCR-Based Fingerprinting - Luciana Piarulli; Michele Antonio Savoia; Francesca Taranto; Nunzio D’Agostino; Ruggiero Sardaro; Stefania Girone; Susanna Gadaleta; Vincenzo Fucili; Claudio De Giovanni; Cinzia Montemurro; Antonella Pasqualone; Valentina Fanelli (Foods, 2019)
Extra virgin olive oil (EVOO) has elevated commercial value due to its health appeal, desirable characteristics and quantitatively limited production, and thus it has become an object of intentional adulteration. As EVOOs on the market might consist of a blend of olive varieties or sometimes even of a mixture of oils from different botanical species, an array of DNA-fingerprinting methods have been developed to check the varietal composition of the blend. Starting from a comparison between publicly available DNA extraction protocols, we set up a timely, low-cost, reproducible and effective DNA isolation protocol, which allows an adequate amount of DNA to be recovered even from commercial filtered EVOOs. Then, in order to verify the effectiveness of the DNA extraction protocol herein proposed, we applied PCR-based fingerprinting methods starting from the DNA extracted from three EVOO samples of unknown composition. In particular, genomic regions harboring nine simple sequence repeats (SSRs) and eight genotyping-by-sequencing-derived single nucleotide polymorphism (SNP) markers were amplified for authentication and traceability of the three EVOO samples. The whole investigation strategy herein described might favor producers in terms of higher revenues and consumers in terms of price transparency and food safety.